'Improving smart medication management': an online expert discussion. Issue 1 (27th April 2022) - Bates, David W; Cheng, Hsiang-Yin; Cheung, NT; Jew, Rita; Mir, Fraz; Tamblyn, Robyn; Li, Yu-Chuan
Abstract : Medication safety continues to be a problem inside and outside the hospital, partly because new smart technologies can cause new drug-related challenges to prescribers and patients. Better integrated digital and information technology (IT) systems, improved education on prescribing for prescribers and greater patient-centred care that empowers patients to take control of their medications are all vital to safer and more effective prescribing. In July 2021, a roundtable discussion was held as a spin-off meeting of the International Forum on Quality and Safety in Health Care Europe 2021 to discuss challenges and future direction in smart medication management. This manuscript summarises the discussion focusing on the aspects of digital and IT systems, safe prescribing, improved communication and education, and drug adherence.